2015
DOI: 10.3389/fmicb.2015.00343
|View full text |Cite
|
Sign up to set email alerts
|

Virulence reduction in bacteriophage resistant bacteria

Abstract: Bacteriophages can influence the abundance, diversity, and evolution of bacterial communities. Several bacteriophages have been reported to add virulence factors to their host and to increase bacterial virulence. However, lytic bacteriophages can also exert a selective pressure allowing the proliferation of strains with reduced virulence. This reduction can be explained because bacteriophages use structures present on the bacterial surface as receptors, which can be virulence factors in different bacterial spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(158 citation statements)
references
References 80 publications
7
149
0
2
Order By: Relevance
“…It would be interesting to know whether new variants emerge in such experiments. Alternatively, some phages driving evolution toward loss of virulence could be favoured if they exist (Leó n & Bastías, 2015). Another concern is the potential role of phages in horizontal transfer, which could be favoured by the longterm maintenance of phage genomes inside the bacteria during pseudolysogeny.…”
Section: Cross-resistance and Reversibility Of Mutantsmentioning
confidence: 99%
“…It would be interesting to know whether new variants emerge in such experiments. Alternatively, some phages driving evolution toward loss of virulence could be favoured if they exist (Leó n & Bastías, 2015). Another concern is the potential role of phages in horizontal transfer, which could be favoured by the longterm maintenance of phage genomes inside the bacteria during pseudolysogeny.…”
Section: Cross-resistance and Reversibility Of Mutantsmentioning
confidence: 99%
“…It has been shown that phage-resistant bacteria lose their virulence during phage therapy (48). In contrast, the virulence of the bacteria may be increased with exposure to phage, according to this study.…”
Section: Resultsmentioning
confidence: 66%
“…Phage resistance most commonly develops through the down-regulation, shielding, or modification of bacterial cell surface receptors required for viral attachment [69,70]. To ensure survival, evolved phages tend to bind to highly conserved surface receptors, such as those required for virulence [71][72][73].…”
Section: Phage Resistancementioning
confidence: 99%
“…In addition, phage resistance is not always detrimental to treatment, because in many cases acquired resistance is costly for the bacterium (e.g. loss of virulence toward their hosts, lower growth rate, decreased lifespan, or loss of the ability to attach or invade to mammalian cells) [70,71,73,75]. In addition, acquiring phage resistance can cause bacteria to become more antibiotic-sensitive [76,77].…”
Section: Phage Resistancementioning
confidence: 99%